Pengaruh Budaya Organisasi dan Lingkungan Kerja terhadap Kinerja Pegawai Pada Badan Pendapatan Daerah - Asike, Ades (Jurnal Ilmiah Multidisiplin Amsir, 2023)
The purpose of this study was to influence organizational culture and work environment on employee performance at the Regional Revenue Agency (BAPENDA) in Sidenreng Rappang Regency. The data collection techniques that researchers used in this study were observation, interviews, questionnaires, documentation. As the population in this study, researchers took employees of the Regional Revenue Agency (BAPENDA) of Sidenreng Rappang Regency with the status of state civil servants. In order for this research to be precise and proportional, it was used, so in this study a sampling technique was used, namely purposive sampling, where the sample was selected based on certain considerations. Thus the number of samples in this study were 43 people. The results of this study indicate that Partially Organizational Culture Variable (X1) has a positive and significant effect on the performance of Regional Revenue Agency employees. Meanwhile, the Work Environment variable (X2) has a positive and significant effect on the performance of Regional Revenue Agency employees and the level of significance is greater. Simultaneously the Variables of Organizational Culture and work environment from the research results have a positive and significant effect.